Nephrogenic diabetes insipidus associated with tenofovir administration: report of a paediatric case - Costa,Miguel (2012)
Tenofovirrenal toxicity, particularly when associated with other antiretrovirals, has been reported in the adult HIV-positive population. Reports in HIVpositive children are very rare. The authors report a paediatric case of nephrotoxicity associated with tenofovir and didanosine, emtricitabine and lopinavirritonavir coadministration. A 12-year-old girl with AIDS (clinical stage C) with a multidrug-resistant virus and several treatment failures initiated emtricitabine, tenofovir, didanosine and lopinavir-ritonavir in 2008 with good tolerance. Her viral load became undetectable and CD4 count normal. Two years later she presented generalized weakness, polydipsia and polyuria. On physical examination dehydration was evident. Her vital signs were stable. She had lost 5% of her body weight in the previous week. Urinalysis revealed a urine gravity of 1000, osmolality 150 mOsm/Kg and no proteinuria or glucosuria. Blood analysis showed osmolality 289 mOsm/Kg, normal values of glucose, creatinine, urea, sodium, potassium, chloride and calcium. A water restriction test followed by desmopressin administration confirmed the diagnosis of nephrogenic diabetes insipidus. Tenofovir and didanosine were stopped and abacavir was added. The patient was treated with a thiazide diuretic and salt restriction. There was good clinical evolution and no relapses. This case highlights important possible side effects of tenofovir and emphasises the need for further studies into the renal safety of this agent in paediatric patients.